Plots, property and behaviour - Kropf , Karl (Urban Morphology, 2017)
There is a lack of clarity in urban morphology in the use of the terms ‘plot’ and ‘lot’. The complications arise in large part because these terms are used to refer to several things. Further ambiguities arise because the concept of property is not univocal, and the boundaries corresponding to the different meanings of plot do not necessarily coincide. An attendant problem is that distinct aspects of urban form are conflated into a single, ill-defined entity. Given the significance of the plot in building typology and urban morphology, the ambiguities in its definition raise questions about the role of the plot in the generation and transformation of urban form and in particular in the central phenomenon of persistence and the differential rates of change between street pattern, plot pattern and building pattern. The aim of this paper is therefore to clarify the terms plot and lot by examining the pertinent characteristics that are used to define them and the underlying relationships and logic they entail. The resolution offered in conclusion is that the fundamental basis for defining a plot – as property and an element of control – is rooted in human behaviour and our interactions with both our environment and each other. This may then provide a fruitful basis for investigating the phenomenon of persistence in more detail.